Evangelicals and the Oxford Movement Centenary. (21st September 2012) - Atherstone, Andrew
<x xml:space="preserve">Abstract</x> The first centenary of the Oxford Movement was celebrated throughout the Anglican Communion in July 1933. Within the Church of England, the commemoration was officially sanctioned by the archbishops of Canterbury and York, a sign of growing rapprochement between the episcopate and the Anglo‐Catholic movement. The triumphant Anglo‐Catholic Congress organized exuberant demonstrations, but amongst the beleaguered Evangelical minority the birthday party caused widespread consternation and protest. The occasion became a battleground between rival interpretations of Anglican identity and competing visions for the future of the Church of England. This article examines Evangelical responses to the 1933 celebrations in England, focusing upon Evangelical contributions to Oxford Movement historiography. In particular, it explores Evangelical answers to two of the key questions concerning Tractarian origins: did the Oxford Movement rescue the Church of England, and did the Oxford Movement complement the Evangelical revival?